Assessment of Annoyance of Traffic Noise Based on Residents’ Subjective Evaluations and Actual Noise Measurements in Environment - Ławniczak, Paulina; Orczyk, Malgorzata (Geomatics and Environmental Engineering, 2024)
The aim of the article is to assess the traffic noise on one of the main streets in the city of Poznań. The authors chose to discuss the topic of evaluating the impact of the sound phenomena that is generated by vehicles in urbanized areas. This decision resulted from the fact that approximately 20% of the EU population live in places where permissible noise levels are exceeded – both during the day and at night. The selected street for the study is precisely such a location; it is characterized by a very high volume of vehicle traffic throughout the day (a road that leads out of the city toward Warsaw) and residential buildings close to it. The research involved residents’ subjective assessments of noise as well as actual noise measurements. The survey addressed issues that were mainly related to residents’ perceptions of the sound phenomena on the street, while the second stage of the research focused on actual noise measurements. A 24-hour measurement of noise and traffic intensity was conducted on the selected street. The results that were obtained in this way allowed for an assessment of the acoustic climate considering applicable regulations and the residents’ experiences. The experimental studies showed that, on Warszawska Street, the equivalent sound levels exceed 71 dB during the day and 68 dB at night. In the survey, 33% of the respondents indicated that living on this street was bothersome due to the noise, with it being most disruptive during the night hours (10:00 p.m.–6:00 a.m.) according to 26% of the responses, and between 12:00 noon and 6:00 p.m. according to 31% of the responses.